Evaluation of Construction Asphalt Pavements Based Toposable Set Theory: A Case Study - Junxia Cai; Hui Li; Zhiwu Li; Qingfu Li (Applied Sciences, 2022)
(1) Background: Because of the unique advantages of asphalt pavements, they occupy a large part of the road system in China and worldwide. The construction of asphalt pavements has provided the necessary conditions for the efficient and rapid development of our economy. At present, the asphalt pavement is damaged prematurely before reaching the designed service life. This paper analyzes the influence of different factors on the construction quality of asphalt pavement in the process of construction control, so as to ensure that the service performance of asphalt pavement is improved and the service life is prolonged. (2) Methods: In this paper, based on the data of two-by-two relative importance comparisons between the indexes by experts, a topologizable interval judgment matrix is constructed and the weights of each index are calculated by single ranking; the model is validated by constructing a comprehensive assessment model of the topologizable set of asphalt pavement construction controls and through a case study. (3) Results: Using the model proposed in this paper, the overall construction control level for the case was calculated to be II, with a variable eigenvalue of 2.4784, which is biased towards level III. It is verified that the model can evaluate the construction control of asphalt pavement more reasonably and scientifically than previous methods. (4) Conclusions: This study can provide a reference for the evaluation of asphalt pavement construction control.